PENDAMPINGAN PIRT DONAT SINGKONG UNTUK KOMUNITAS IBU-IBU DI KAMPUNG CAHAYA, JAKARTA - Asep Maksum; Nadya Mara Adelina; Anggun Pratiwi; Aisyah Arsyad (UIN Sunan Kalijaga, 2024)
In 2023, community service activities in Kampung Cahaya faced challenges in producing cassava donuts. Specifically, the donuts were not durable, lacked a distribution permit (P-IRT number), and were being marketed in a limited manner. To address these issues, it is essential to develop more standardized product innovations that are both feasible for production and suitable for sale. The proposed solution is to obtain a P-IRT permit for the women of Kampung Cahaya Village to standardize their cassava donut products. This initiative aims to assist these women in meeting product standards by using packaging labels that comply with regulatory requirements and ensuring that their production facilities meet all necessary inspection criteria. The implementation of this community service project involves two main stages: (1) Development of the knowledge and skills of women regarding effective processing systems and standards for frozen cassava donuts, and (2) Training on food safety and product permitting. The outcomes of these community service activities have led to improvements in the standardization of donut products, including the use of compliant packaging labels and enhancements in production techniques and facilities to meet established standards. ============================================================== Hasil kegiatan pengabdian masyarakat pada tahun 2023 pembuatan produk donat singkong di Kampung Cahaya terdapat kendala yaitu produk donat yang tidak tahan lama dan belum memiliki izin edar (nomor P-IRT) serta masih dipasarkan secara terbatas. Untuk itu diperlukan inovasi produk yang lebih terstandar untuk layak diproduksi dan layak dijual. Solusi yang ditawarkan adalah pembuata izin P-IRT donat singkong untuk Ibu-Ibu di Kampung Cahaya. Tujuan dari kegiatan ini adalah memberikan pendampingan kepada Ibu-Ibu di Kampung Cahaya dalam standarisasi produk donat singkong dengan penggunaan label kemasan yang telah memenuhi kriteria label serta hasil pemeriksaan sarana produksi yang telah memenuhi standar persyaratan yang ditetapkan. Pelaksanaan abdimas pendampingan pengurusan P-IRT di Kampung Cahaya dilakukan dalam 2 tahap utama, yaitu (1) Pengembangan kualitas dan wawasan SDM Ibu-Ibu mengenai sistem dan standar pengolahan produk donat singkong frozen yang baik, (2) pelatihan keamanan pangan dan izin produk. Hasil pelaksanaan kegiatan Abdimas pendampingan pengurusan P-IRT memberikan perubahan standarisasi produk donat dengan penggunaan label kemasan yang telah memenuhi kriteria label dan perubahan teknik sertal sarana produksi yang telah memenuhi standar persyaratan yang ditetapkan.